2022
DOI: 10.1111/jfpp.17264
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of pine cone molasses (pekmez) from Pinus nigra and Pinus brutia in Osmaniye

Abstract: The ingredients and components of herbal resources are of great importance in terms of medicinal/aromatic properties. It is stated that the existence of various diseases, the use of plants for their treatment and the specific properties of each are increasing day by day (Baytop, 1999). The variety of products obtained from these herbal sources especially forest plants which can be consumed as food and transformed into commercial products is increasing nowadays.The Pinaceae family has the most species in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…These results illustrate the richness of pinecones in sugars and the in uence of the solvent used on their extraction. Compared to the literature, the study by Gamli et al [11] showed that the cones of PB contain between 22.41 and 22.97% of the total sugars in the aqueous extract.…”
Section: Reducing Sugar Contentmentioning
confidence: 86%
“…These results illustrate the richness of pinecones in sugars and the in uence of the solvent used on their extraction. Compared to the literature, the study by Gamli et al [11] showed that the cones of PB contain between 22.41 and 22.97% of the total sugars in the aqueous extract.…”
Section: Reducing Sugar Contentmentioning
confidence: 86%
“…The use of medicinal plants is of great importance in terms of various phenolics in treating various diseases, and it has been increasing recently. The products obtained from plant resources, especially forest plants, also increase daily (Gamli, 2022). The Pinaceae family has the highest number of species and is widely distributed in Asia, North America, Europe, and the Northern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%